Rapid desensitization of somatodendritic 5-HT(1A) receptors by chronic administration of the high-efficacy 5-HT(1A) agonist, F13714: a microdialysis study in the rat - Assié, M-B (Nature Publishing Group, 2006)
BACKGROUND AND PURPOSE: Desensitization of somatodendritic 5-HT(1A) receptors is involved in the mechanism of action of several antidepressants, but the rapidity of this effect and the amount of agonist stimulation needed are unclear. We evaluated the capacity of the high-efficacy 5-HT(1A) agonist, F13714 (3-chloro-4-fluorophenyl-(4-fluoro-4-{[(5-methyl-6-methylamino-pyridin-2-ylmethyl)-amino]-methyl}-piperidin-1-yl-methanone) and of the partial agonist, flesinoxan, to desensitize somatodendritic 5-HT(1A) receptors involved in the control of 5-HT release. EXPERIMENTAL APPROACH: Intracerebral microdialysis in the hippocampus of freely moving rats was used to examine the acute and chronic effects of the two compounds (administered by osmotic pumps for 3, 7 or 14 days) on extracellular 5-HT levels, measured by HPLC with electrochemical detection. KEY RESULTS: When given acutely, F13714, flesinoxan and the low-efficacy 5-HT(1A) agonist, buspirone, dose-dependently decreased extracellular 5-HT concentrations (ED(50) values: 0.04, 0.77 and 5.6 mg kg(−1), respectively). The selective 5-HT(1A) antagonist WAY100635 inhibited the effects of the three compounds. F13714 (2.5 mg kg(−1) per day for 3, 7 or 14 days and 0.63 mg kg(−1) for 7 days) significantly attenuated the inhibition of 5-HT release induced by buspirone (10 mg kg(−1)). In contrast, flesinoxan (10 mg kg(−1) per day) failed to alter the response to buspirone at any of the treatment durations. Conclusions and implications: Rat somatodendritic 5-HT(1A) receptors controlling hippocampal 5-HT release were rapidly desensitized by chronic activation with a high-efficacy 5-HT(1A) agonist, but not by chronic activation with a partial agonist. Thus, rapid 5-HT(1A) autoreceptor desensitization by high-efficacy agonists may accelerate the onset of the therapeutic effects of antidepressants.